2012
DOI: 10.1111/j.1440-1797.2012.01662.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D does not improve the metabolic health of patients with chronic kidney disease stage 3–4: A randomized controlled trial

Abstract: Supplementation with cholecalciferol in CKD 3-4 results in appreciable increases in 25-hydroxyvitamin D concentrations, but does not increase insulin sensitivity. The insulin resistance observed was similar among age-, sex- and body mass index-matched individuals with and without CKD. Whether renal dysfunction per se has any influence on the insulin sensitivity of an individual should be the subject of future work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…Overall, our systematic review and meta-analysis of 35 RCTs with a total of 43,407 patients found no evidence for the use of vitamin D 3 supplementation to prevent diabetes in individuals without diabetes, or to reduce insulin resistance and hyperglycemia in those with prediabetes or established type 2 diabetes. The lack of benefit was consistent across study populations, vitamin D dose, and trial quality.…”
Section: Discussionmentioning
confidence: 75%
“…Overall, our systematic review and meta-analysis of 35 RCTs with a total of 43,407 patients found no evidence for the use of vitamin D 3 supplementation to prevent diabetes in individuals without diabetes, or to reduce insulin resistance and hyperglycemia in those with prediabetes or established type 2 diabetes. The lack of benefit was consistent across study populations, vitamin D dose, and trial quality.…”
Section: Discussionmentioning
confidence: 75%
“…Many studies have evaluated vitamin D (either cholecalciferol or ergocalciferol) as a treatment for vitamin D insufficiency or SHPT in adults with predialysis CKD [25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42]. Most were open-label studies and some were conducted in patients exhibiting SHPT.…”
Section: Discussionmentioning
confidence: 99%
“…Most were open-label studies and some were conducted in patients exhibiting SHPT. Only 9 were conducted with concurrent placebo or untreated control groups [34,35,36,37,38,39,40,41,42]. Vitamin D therapy produced modest or transient increases in serum 25-hydroxyvitamin D (generally 10-15 ng/ml), leaving a considerable proportion of the treated patients (up to ∼50%) showing no clinically meaningful increases in serum 25-hydroxyvitamin D or decreases in plasma iPTH.…”
Section: Discussionmentioning
confidence: 99%
“…More recent meta‐analyses concluded that there was no overall effect of vitamin D supplementation on diabetes mellitus‐related outcomes . Newer randomized controlled trials (RCTs) have had inconsistent results, with some reporting positive effects on fasting glucose, HOMA‐IR values and HbA1c, while others did not . In light of the inconclusive evidence, we aimed to assess the effect of vitamin D supplementation on indexes of glycaemic control in a cohort of mainly obese patients with arterial hypertension.…”
Section: Introductionmentioning
confidence: 99%